Focal Prostate Stereotactic Body Radiation Therapy With Correlative Pathological and Radiographic-Based Treatment Planning - Fredman, Elisha; Traughber, Bryan; Kharouta, Michael; Podder, Tarun; Lo, Simon; Ponsky, Lee; MacLennan, Gregory; Paspulati, Raj; Ellis, Bradley; Machtay, Mitchell; Ellis, Rodney (Frontiers in Oncology, 2021)
Introduction: Advances in multiparametric MRI (mpMRI) combining anatomic and functional imaging can accurately identify foci of adenocarcinoma within the prostate, offering the possibility of partial gland therapy. We performed tandem prospective pilot trials to investigate the feasibility of focal prostate SBRT (f-SBRT) based on correlating diagnostic mpMRI and biopsies with confirmatory pathology in treatment planning. Materials and Methods: Patients with pathologic focal Gleason 6-7 disease and a corresponding PIRADS 4-5 lesion on mpMRI underwent targeted and comprehensive biopsies using MRI/ultrasound fusion under electromagnetic sensor navigation. After rigorous analysis for imaging-biopsy concordance, 5/18 patients were eligible to proceed to f-SBRT. Chi squared test was used for differences from expected outcomes and concordance was estimated with binomial distribution theory and Wilson’s method. Results: Six patients had Gleason 6 and 12 had Gleason 3+4 disease (mean PSA: 5.8 ng/mL, range 2.2-8.4). Absolute concordance was 43.8% (95% CI of 0.20, 0.64). Patterns of discordance included additional sites of ipsilateral disease, bilateral disease and negative target. Five were upstaged to a new NCCN risk category necessitating treatment escalation. The five patients with concordant pathology completed 3-fraction f-SBRT with sparing of the surrounding normal structures (including contralateral neurovascular bundle), with no reported Grade 2+ toxicities and favorable PSA responses (mean 41% decrease). Conclusions: On our pilot trials of f-SBRT planning using rigorous imaging and pathology concordance, image-guided confirmatory biopsies frequently revealed additional disease, suggesting the need for caution in partial-gland therapy. For truly focal disease, f-SBRT provided excellent dosimetry, minimal toxicity and encouraging biochemical response.